Analisa sumur resapan untuk mereduksi limpasan permukaan pada Perumahan Hang Tuah Cipta Residence Pekanbaru - Gandung Rahmadi; Imam Suprayogi; Joleha Joleha (Pelantar Press, 2021)
Changes in land use, namely from cultivated land to closed land or settlements, make the water demand in the area increase, if the water that comes out is not balanced with the water that enters the ground, it will cause a decrease in the ground water level. Another problem that arises due to changes in land use is runoff, where runoff occurs due to rainfall exceeding the suction power or infiltration of the soil, so that over time the runoff becomes a puddle and can even cause flooding. One way to overcome these problems is to apply infiltration wells. This case study takes place in the Hang Tuah Cipta Residence Housing Area, Pekanbaru. From the results of field research and Hydrological data analysis revealed that the main existing drainage channel discharge with a discharge capacity of 0.923 m³/s is unable to accommodate the discharge that occurs at 1.19 m³/s. Segment or secondary drainage channels Q12 and Q13 are also unable to accommodate the discharge that occurs at 0.085 m³/s with a capacity of 0.06 m³/s. Based on the analysis results it is planned that the infiltration well with a radius of 0.5 m and a depth of 9 m which has a capacity of 0.0022 m³/s. After the planned discharge infiltration well comes out to be 0.88 m³/s, it means that the discharge does not exceed drainage capacity of 0.923m³/s.